Politeness Utterances In Teaching Learning English Process - elim trika sudarsih (UKI TORAJA, 2016)
Successful communication is the joint product of linguistic as well thesociolinguistic competence, with the latter competence denoting appropriatenesswhich is closely associated with politeness. The study aimed to investigate thepoliteness utterances in teaching learning process by teacher at SMK HARAPANTORAJA. Data were collected from teacher and students in teaching learningEnglish process. Data analysis consisted of analysis politeness utterances inlearning teaching process between teacher and students. The result of theresearch found that teacher call the students’ name directly, the teacher usedpronoun mu, kamu, kau it is polite because teacher has higher position anddifferent status than students.